Risk Factors and Clinical Profile of Respiratory Distress in Newborn: A Hospital Based Study in Bangladesh Army (Bangladesh Medical Journal, 2021)
Neonatal respiratory distress (NRD) is a main cause of neonatal morbidity and mortality in developing countries. Early detection of its risk factors and early treatment of its causes are major challenges. There are many causes of respiratory distress, among them, transient tachypnea of newborn (TTN), respiratory distress syndrome (RDS) and perinatal asphyxia are commonest causes. Timely and appropriate therapy is essential to prevent ongoing injury and improve outcome. The aim of this study was to determine the risk factors and to identify the causes of respiratory distress in neonatal intensive care unit (NICU) in Combined Military hospital (CMH) Sylhet and to observe the hospital outcome of these babies. Descriptive type of cross- sectional study was conducted in CMH Sylhet over a period of one year from April 2018 to March 2019. During the study period a total of 287 live newborns were found and included as study subjects to observe for development of respiratory distress. The overall prevalence of respiratory distress was 19.2%. There was male predominance (63.6%) and more than two third (71.1%) were born by cesarean section. Prematurity (38.2%), low birth weight (52.7%), male gender (63.6%), APGAR at 1 min